Corporate Social Responsibility as a key to fight labour inequality: Clave para combatir la desigualdad laboral - Espinel González, María Almudena (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Inequalities are still very present in the current Spanish labour market. That is why, after this study, different approaches to fight them will be proposed, putting the bet on a new business model in which two of the three pillars of Corporate Social Responsibility are strengthened: equality and sustainability, since investing in equality is a challenge but a great success for achieving the development of well-being and the economic growth of a country